2020
DOI: 10.1049/iet-its.2019.0655
|View full text |Cite
|
Sign up to set email alerts
|

Study on intelligent algorithm of guide partition for emergency evacuation of a subway station

Abstract: In order to improve the efficiency of emergency evacuation of subway passengers, the concept of ‘guide partition’ is put forward, and an intelligent algorithm of guide partition for emergency evacuation of subway stations is proposed according to the theory of allocation problem in operational research. First an evacuation partition optimization algorithm based on the shortest path principle and based on exit capacity for non‐standard allocation problem is proposed, according to the solution of service facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Evacnet [73] and CFAST [74] are example of simulation software with fine grid models. Building Exodus [75] and Simulex [76] are examples of simulation software with rough grid models. Legion [77] and Pathfinder [78] are examples of simulation software with continuous models.…”
Section: Evacuation Modelsmentioning
confidence: 99%
“…Evacnet [73] and CFAST [74] are example of simulation software with fine grid models. Building Exodus [75] and Simulex [76] are examples of simulation software with rough grid models. Legion [77] and Pathfinder [78] are examples of simulation software with continuous models.…”
Section: Evacuation Modelsmentioning
confidence: 99%
“…In terms of planning escape path based on an algorithm model, Zheng et al proposed an invasive weed optimization algorithm, which has obvious advantages in convergence speed and evacuation time of crowd emergency evacuation simulation and effectively improves crowd emergency evacuation performance [ 28 ]. To improve the efficiency of emergency evacuation of subway passengers, Wang et al suggested the concept of “guiding and platoon partition” and an intelligent algorithm of guiding and shunting for emergency evacuation of subway stations [ 29 ]. Zhu et al adopted the lasso regression method to consider the road factors in pedestrian speed.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction: Indoor navigation models can express geometric, semantic, and topological information about indoor built environments; furthermore they are important tools in indoor facility management, emergency response [1], and pedestrian location and navigation [2]. Existing research on indoor navigation models in indoor settings has predominantly focused on graph-based network models [3][4][5].…”
mentioning
confidence: 99%